Total quality management, performance, appraisal and training: Selected issues and implications - Halachmi, Arie (1996)
The author discusses TQM, claims on its inconsistency with existing performance appraisal practices, reviews some issues involving use of training to prepare for TQM as a tool for planned change with an overriding word of caution that without understanding human ecology of public agencies, TQM may not deliver the promised improvements in productivity. - Reproduced
Keywords: Training; Performance appraisal; Civil service; Total quality management